Environmental and microbial factors influencing methane and nitrous oxide fluxes in Mediterranean cork oak woodlands: trees make a difference - Shvaleva, Alla; Siljanen, Henri M. P.; Correia, Alexandra; Costa e Silva, Filipe; Lamprecht, Richard E.; Lobo-do-Vale, Raquel; Bicho, Catarina; Fangueiro, David; Anderson, Margaret; Pereira, João S.; Chaves, Maria M.; Cruz, Cristina; et al. (Frontiers in Microbiology, 2015)
Cork oak woodlands (montado) are agroforestry systems distributed all over the Mediterranean basin with a very important social, economic and ecological value. A generalized cork oak decline has been occurring in the last decades jeopardizing its future sustainability. It is unknown how loss of tree cover affects microbial processes that are consuming greenhouse gas fluxes in the montado ecosystem. The study was conducted under two different conditions in the natural understory of a cork oak woodland in center Portugal: under tree canopy (UC) and open areas without trees (OA). Fluxes of methane and nitrous oxide were measured with a static chamber technique. In order to quantify methanotrophs and bacteria capable of nitrous oxide consumption, we used quantitative real-time PCR targeting the pmoA and nosZ gene encoding the subunit of particulate methane mono-oxygenase and catalytic subunit of the nitrous oxide reductase, respectively. A significant seasonal effect was found on CH4 and N2O fluxes and pmoA and nosZ gene abundance. Tree cover had no effect on methane fluxes; conversely, whereas the UC plots were net emitters of nitrous oxide, the loss of tree cover resulted in a shift in the emission pattern such that the OA plots were a net sink for nitrous oxide. In a seasonal time scale, the UC had higher gene abundance of Type I methanotrophs. Methane flux correlated negatively with abundance of Type I methanotrophs in the UC plots. Nitrous oxide flux correlated negatively with nosZ gene abundance at the OA plots in contrast to that at the UC plots. In the UC soil, SOM had a positive effect on soil extracellular enzyme activities (EEA), which correlated positively with the N2O flux. Our results demonstrated that tree cover affects soil properties, key enzyme activities and abundance of microorganisms and, consequently net CH4 and N2O exchange.